Impact of Aeolian Dry Deposition of Reactive Iron Minerals on Sulfur Cycling in Sediments of the Gulf of Aqaba - Blonder, Barak; Boyko, Valeria; Turchyn, Alexandra V.; Antler, Gilad; Sinichkin, Uriel; Knossow, Nadav; Klein, Rotem; Kamyshny, Alexey (Frontiers in Microbiology, 2017)
The Gulf of Aqaba is an oligotrophic marine system with oxygen-rich water column and organic carbon-poor sediments (≤0.6% at sites that are not influenced by anthropogenic impact). Aeolian dust deposition from the Arabian, Sinai, and Sahara Deserts is an important source of sediment, especially at the deep-water sites of the Gulf, which are less affected by sediment transport from the Arava Desert during seasonal flash floods. Microbial sulfate reduction in sediments is inferred from the presence of pyrite (although at relatively low concentrations), the presence of sulfide oxidation intermediates, and by the sulfur isotopic composition of sulfate and solid-phase sulfides. Saharan dust is characterized by high amounts of iron minerals such as hematite and goethite. We demonstrated, that the resulting high sedimentary content of reactive iron(III) (hydr)oxides, originating from this aeolian dry deposition of desert dust, leads to fast re-oxidation of hydrogen sulfide produced during microbial sulfate reduction and limits preservation of reduced sulfur in the form of pyrite. We conclude that at these sites the sedimentary sulfur cycle may be defined as cryptic.